Oleaster seed-derived activated carbon/ferrite nanocomposite for microwave absorption in the X-band range - Mahmoodi, Mahsa; Aslibeiki, Bagher; Peymanfar, Reza; Naghshara, Hamid (Frontiers in Materials, 2022)
Conjugated carbonaceous structures achieved from biological materials were significantly considered electromagnetic waveabsorbing materials due to their eye-catching dielectric, lightweight, low-cost, and chemical stability features. To strengthen the microwave absorbing performance of the porous carbon (Oleaster seeds), Fe3O4 magnetic nanoparticles have been successfully anchored onto the surface of biomass-derived material through a co-precipitation method. Noticeably, the dielectric constant, impedance matching, permeability, and microwave absorbing capability were improved by changing the carbon content. The optimized Fe3O4/activated carbon (AC) illustrated the excellent electromagnetic wave absorption performances with a maximum reflection loss (RL) value of -51.12 dB and an effective absorption bandwidth of ~4 GHz (RL < 10 dB) with a thickness of 1 mm. The promoted microwave absorbing characteristics of Fe3O4/AC composites are rooted in improved impedance matching, eddy current loss, natural and exchange resonance, andspecific surface area,bringing more polarization loss andmultiple reflection and scattering. The presented research shed new light on the fabrication of practical microwave-absorbing materials based on biomass-derived materials with a facile experimental procedure.